Out of the dust eaudiobook - Hesse, Karen (Listening Library, 2007)
Billie Jo has a great deal to forgive: her father for causing the accident that killed her mother; her mother for leaving when Billie Jo needed her most; and herself for being the cause of her own sorrow. Daddy's too wrung out to help her, and there's no one else to care. So at fourteen, Billie Jo must heal herself - even if it means tearing up her roots and leaving behind everything she's ever known.